Stronger niche than dispersal effects on α‐ and β‐diversity of stream algae, insects, and fish across latitudes in the United States. Issue 12 (2nd October 2022) - Mruzek, Joseph L.; Budnick, William R.; Larson, Chad A.; Luc, Dinh K.; Passy, Sophia I.
Abstract: Aim: Niche and dispersal processes influence biodiversity, but their relative importance along latitude is unclear. We predicted that: (a) niche processes would dominate at high latitudes due to increased climatic stress, consistent with the physiological tolerance hypothesis and the Dobzhansky–MacArthur hypothesis and (b) dispersal limitation would prevail at low latitudes due to narrower niches and smaller range sizes, as postulated by the dispersal–ecological specialization trade‐off hypothesis, the latitude–niche breadth hypothesis, and Rapoport's rule. Location: Central United States. Time period: 1993–2019. Major taxa studied: Stream algae, insects, and fish. Methods: We examined the relative effects of environment (climate and physicochemistry) versus space on stream biodiversity in seven latitudinal zones, spanning 19 latitudinal degrees. In each zone, species richness (α‐diversity) was analysed with multiple regression and variance partitioning. Compositional dissimilarity (β‐diversity) within zones was assessed with distance‐based redundancy analysis (dbRDA) and variance partitioning. Results: For α‐diversity, latitudinal variability of niche and dispersal processes conformed to our predictions in all three groups, except for dispersal processes in insects. However, the drivers of β‐diversity did not follow our predictions. The latitude–niche breadth hypothesis and Rapoport's rule were weakly supported only in fish. Main conclusions: The importance of niche and dispersal processes varied predictably along the latitudinal gradient only for α‐diversity. However, the niche effects were driven mostly by physicochemistry, and the dispersal effects were not always linked with ecological specialization and range size. This suggests that climate‐based biodiversity theories do not have particular relevance for the streams in our study. Niche processes had a greater impact than dispersal processes across species groups and diversity metrics, emphasizing the primary role of the environment.